Health education to promote knowledge about sickle cell disease and newborn screening in pregnant women: a community-based pilot study using the healthy beginning initiative - Osita U. Ezenwosu; John O. Olawepo; Lorraine J. Lacroix-Willliamson; Ijeoma U. Itanyi; Amaka Ogidi; Tonia C. Onyeka; Madeline Gully; Maisha Gregory; Janis L. Breeze; Stephanie Ibemere; Ngozi Idemili-Aronu; Beth E. Molnar; et al. (BMC, 2024)
Abstract Background Pregnancy presents a critical period for any maternal and child health intervention that may impact the health of the newborn. With low antenatal care attendance by pregnant women in health facilities in Nigeria, community-based programs could enable increased reach for health education about sickle cell disease (SCD) and newborn screening (NBS) among pregnant women. This pilot study aimed to assess the effect of education on the knowledge about SCD and NBS among pregnant women using the Healthy Beginning Initiative, a community-based framework. Methods A pre-post study design was used to evaluate knowledge of SCD and NBS in a convenience sample of 89 consenting pregnant women from three communities. Participants were given surveys prior to and following completion of a health education session. McNemar's test was used to compare the proportion of participants with correct responses. The level of significance was taken as p < 0.05. Results Compared to pre-test values, post-test values showed that participants understood that SCD is hereditary (93.3% vs. 69.7%), both parents must have at least one gene for someone to have SCD (98.9% vs. 77.5) and blood test is the right way to know if one has SCD (98.8% vs. 78.7%). Also, a large proportion of participants (post-test ~ 89.9%; compared to pre-test ~ 23.6%) understood that the chance of conceiving a child with SCD was 25% for a couple with the sickle cell trait (SCT). Knowledge of the possibility of diagnosing SCD shortly after birth was highly increased in the post test phase of the study when compared to the pre-test phase (93.3% vs. 43.9%, respectively). Concerning the overall knowledge scores, those with high level of knowledge significantly increase from 12.6% pretest to 87.4% posttest (p = 0.015). Conclusion The health education intervention was associated with significant improvement on almost all measures of SCD knowledge. Focused health education for pregnant women using community structures can improve knowledge of SCD and NBS.